A fuzzy approach for the intuitionistic multi-objective linear fractional programming problem using a bisection method - Kara, Nurdan; Kocken, Hale Gonce; Akdemir, Hande Gunay (SPRINGER, 2025)
In this paper, intuitionistic fuzzy multi-objective linear fractional programming problems (IFMOLFPs) with several fractional criteria, including profit/cost, profit/time, or profitability ratio maximization, are considered. Moreover, all parameters, with the exception of the decision variables, are characterized as triangular intuitionistic fuzzy numbers. The component-wise optimization method is employed to transform IFMOLFP into an equivalent crisp multi-objective linear fractional problem. Then, we use an iterative fuzzy methodology that integrates linear programming with a bisection approach. The proposed approach addresses single-objective and real-life multi-objective organizational planning problems, which are approached using various methods in the literature. It is used for non-linear membership functions in solving these problems. Furthermore, the values obtained using the ranking function are compared. Ultimately, the decision-maker selects the most appropriate solution technique based on the weights of the objective functions.
Keywords: Multi-objective linear programming; Fractional programming; Fuzzy programming; Intuitionistic fuzzy number; Bisection method; Membership function; DECISION-MAKING; MODEL; Computer Science; Mathematics